Once more on the origin of Lith. auka - Kabašinskaitė, Birutė (Baltistica, 2016)
This article aims to show that the origin of the words aukauti ‘sacrificeʼ, auka ‘sacrifice, donationʼ and aukuras ‘sacrificial siteʼ goes back to the 19th century. These are the transformations and new formations by Simonas Daukantas. The word aukuoti ‘rock, heave’ was assigned the contextual meaning of ‘to make a heave offering’ by the editors of Bretkūnas’ Bible. Daukantas made use of the words aukuoti, aukavimas in this particular sense; he is likely to have taken them as substitutes for Slavisms apieravoti, apiera from Milkus’ (Mielcke) dictionary. Daukantas unconsciously altered the infinitive form of the verb (aukauti) and provided a peculiar interpretation of the word itself, he saw a different motivation for the act of aukauti, that of calming, pacifying the gods (the purpose of the offering rather than its manner). This is shown by the specific collocability of aukauti coinciding with the valency of maldyti, raminti ‘appease, soothe’ as well as some word collocations used by Daukantas. However, already in the Istorija žemaitiška (Samogitian History) where Daukantas’ remake aukauti was first used, a different valency (the same as in the modern language) of this verb was encountered; it was determined by the influence of synonymous Slavisms apiera, apieravoti. The article also discusses the formation of the neologisms auka, aukas and aukuras.